2015
DOI: 10.1519/jsc.0000000000000640
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Aerobic and Anaerobic Capacities of Elite Cyclists From Changes in Lactate During Isocapnic Buffering Phase

Abstract: This study predicted aerobic and anaerobic capacities using relative changes of arterial blood lactate during the isocapnic buffering phase (relative [La]ISBP). Fourteen male professional cyclists (sprint-trained [n = 6] and endurance [n = 8]) performed 2 exercise sessions to exhaustion on a cycle ergometer; 1 incremental standard test to determine the isocapnic buffering phase, buffering capacities, and relative [La]ISBP and 1 supramaximal exercise test to determine maximal accumulated oxygen deficit (MAOD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 26 publications
2
23
0
2
Order By: Relevance
“…During the ICB phase, more H + has been reported to be buffered by the non-bicarbonate buffer system in sprint-trained cyclists than in endurance cyclists (8). Depending on differences in the metabolic pathways used during training sessions, the AT, the RCP and consequently the ICB phase varies between aerobic-and anaerobic-trained athletes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…During the ICB phase, more H + has been reported to be buffered by the non-bicarbonate buffer system in sprint-trained cyclists than in endurance cyclists (8). Depending on differences in the metabolic pathways used during training sessions, the AT, the RCP and consequently the ICB phase varies between aerobic-and anaerobic-trained athletes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, according to some researchers, the ICB is not related to endurance performance (11). Recently, it has been shown that the relative ICB phase can be useful for predicting both the aerobic and anaerobic capacities in athletes (8).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations